2022
DOI: 10.2141/jpsa.0200069
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Selenium Given as Dietary Supplements Accumulate in Tissues and Semen and Improve Reproductive Parameters in Older Red Cornish

Abstract: The reproductive performance of broiler breeder chickens noticeably decreases toward the end of their commercial lives. Herein, we determined the effects of vitamin E and selenium dietary supplementation on semen traits, egg fertility (defined as fertilization and hatching rates) of adult (49-week-old) and older (63-week-old) Red Cornish breeders. We found that both vitamin E and selenium were concentrated in the liver and adipose tissue of adult and older Red Cornish breeders, and were transferred to the seme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
1
0
1
Order By: Relevance
“…In our study, the addition of OH‐SeMet increased the percentage of motility and sperm viability of old roosters and decreased the percentage of abnormality. In line with the results of this study, it has recently been shown that supplementation of organic Se in the diet of roosters improves sperm motility and viability (Bălăceanu et al., 2022 ). In another study, the addition of yeast Se to the diet of broiler breeder roosters (52 weeks old) showed that this compound improves sperm motility, viability and plasma membrane integrity (Raei et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the addition of OH‐SeMet increased the percentage of motility and sperm viability of old roosters and decreased the percentage of abnormality. In line with the results of this study, it has recently been shown that supplementation of organic Se in the diet of roosters improves sperm motility and viability (Bălăceanu et al., 2022 ). In another study, the addition of yeast Se to the diet of broiler breeder roosters (52 weeks old) showed that this compound improves sperm motility, viability and plasma membrane integrity (Raei et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The research revealed that the amount of vitamins A and E eliminated through the seminal plasma increases in the case of the vitamin supplemented roosters, again higher concentrations in the case of vitamin E. This could explain the improvement of some biological properties (motility, for example) of the spermatozoa in the vitamin supplemented groups. Previous studies of Bălăceanu et al (2022) revealed similar accumulations of vitamin E in liver and adipose tissue, but at a dietary intake of about four times higher. Our study reveals that vitamin E is stored in similar amounts even in the case of a quantitatively reduced, but long-term dietary intake.…”
Section: Resultsmentioning
confidence: 60%
“…Включення Селену до складу комбікормів поліпшує здоров'я, підвищує яєчну продуктивність промислового стада птиці та ефективність використання нею кормів (Muhammad et al, 2021). Оптимізація селенового живлення птиці позитивно впливає на інкубаційні якості яєць, зокрема сприяє підвищенню їх заплідненості, виводимості та виведення молодняку, а також покращує якість сперми як у молодих, так і старих самців (Zia et al, 2016;Bălăceanu et al, 2022).…”
Section: вступunclassified